Núcleo de Extensão e Pesquisas Antirracistas e Anticapacitistas - NEPARC - Ramos de Souza, Ana Paula; Bastos Lummertz, Ângela Cristina; de Lara Nunes, Anilton Junior; Lima Costa, Beatriz; da Silva Abreu, Eliane Margarete; Nogueira, Fernanda; do Nascimento Rasquinha, Gabrielle; dos Reis Rezende, Giano; Rosa Pumes, Guilherme; Klauck Magedanz, Joana Carolina; et al. (Revista da Extensão, 2024)
Núcleo de Extensão e Pesquisas Antirracistas e Anticapacitistas - NEPARC